2023
DOI: 10.21203/rs.3.rs-2501974/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Construction and evaluation of clinical prediction model for immunotherapy-related adverse events and clinical benefit in cancer patients receiving immune checkpoint inhibitors based on serum cytokine levels

Abstract: Background: Immune checkpoint inhibitors (ICIs) have revolutionized the therapeutic landscape of cancer. The aim of this study was to develop novel risk classifiers to predict the risk of irAEs and probability of clinical benefits of these individuals. Methods: The cancer patients received ICIs from the First Affiliated Hospital of Xi 'an Jiaotong University from November 2020 to October 2022 were collected and followed up. The logistic regression analyses were adopted to identify independent predictive factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…28,29 In contrast, baseline demographic, clinicopathology, and treatment information in combination with laboratory test results are the most convenient and available predictive factors. Recently, Zhao et al 30 In our research, 81 patients experienced 112 irAEs treated with ICIs in which thyroid dysfunction was the most common irAEs (n = 38, 33.9%), followed by ICI pneumonitis (n = 24, 21.4%), and rash (n = 20, 17.9%). Similar with above, data from a systematic review showed that pneumonitis, hypothyroidism, arthralgia, and vitiligo were more common with patients treated by PD-1 inhibitors.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…28,29 In contrast, baseline demographic, clinicopathology, and treatment information in combination with laboratory test results are the most convenient and available predictive factors. Recently, Zhao et al 30 In our research, 81 patients experienced 112 irAEs treated with ICIs in which thyroid dysfunction was the most common irAEs (n = 38, 33.9%), followed by ICI pneumonitis (n = 24, 21.4%), and rash (n = 20, 17.9%). Similar with above, data from a systematic review showed that pneumonitis, hypothyroidism, arthralgia, and vitiligo were more common with patients treated by PD-1 inhibitors.…”
Section: Discussionmentioning
confidence: 64%
“…Secondly, emerging irAEs-related biomarkers such as chemokines and cytokines were not included in the establishment of our prediction model, which needs to be further explored. 30,52 Finally, the internal validation we applied in our study may not be sufficient compared to the external validation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation